Making technology work in schools : how PK-12 educators can foster digital-age learning - Green, Timothy D., 1968-; Donovan, Loretta C.; Peerless Green, Jody (New York, NY : Routledge, 2025)
Making Technology Work in Schools is an easy-to-use guide for transforming your school into a learner-centered, tech-supportive environment. School systems are increasingly adopting ambitious new educational technologies, but how do you make sure they are yielding effective teaching and learning experiences? The authors' proven, intuitive practices speak directly to academic coaches, school technology leads, district technology directors, and teachers on special assignment who are responsible for introducing new digital tools and programs. Retaining its substantive focus on educational change and the comprehensive PURPOSE Framework, this refreshed second edition updates its real-world examples, practical strategies, and technology categories while adding new content on schoolwide initiatives, needs analysis, professional development, leadership and coaching standards, and more. After reading this book, you will be able to better prepare the educators whom you serve to empower their learners, whether digitally savvy or not, to be engaged, collaborative, and ready for college and careers.
Part I: The Why of Educational Change and Innovation Adoption1. Focusing on the Why 2. The Why of Educational Change and Innovation Adoption 3. A Primer on Educational Change 4. Talking the Talk of Educational Change 5. Different Perspectives on ChangePart II: The How of Educational Change and Innovation Adoption: Learners, Technology, and Instructional Practices6. An Ecological Perspective on Teaching and Learning 7. Teacher Self-Efficacy and Collective Teacher Efficacy 8. The iMakers 9. Digital Technology 10. Instructional PracticesPart III: The What of Educational Change and Innovation Adoption: The PURPOSE Framework11. An Overview of the PURPOSE Framework 12. Phase One: Planning 13. Phase Two: Understanding 14. Phase Three: Researching 15. Phase Four: Preparing 16. Phase Five: Operationalizing 17. Phase Six: Sustaining 18. Phase Seven: Evaluating References
Keywords: Educational technology; EDUCATION / General; EDUCATION / Administration / General; EDUCATION / Distance Education & Learning